Shared Resilience in the Shared Traumatic Reality of Applied Psychologists: the Ukrainian Experience and the Best Practices of the European Union - Zasiekina, Larysa; Burtsan, Volodymyr (Psychological Prospects Journal, 2023)
Purpose. The study aims to theoretically and empirically study the shared resilience in applied psychologists at the beginning of their professional career, as well as to study the best practices of the European Union for the development of shared resilience. Methods. The study applies a set of standardized measures: the Shared Traumatic and Professional Posttraumatic Growth Scale (STPPG) (Tosone 2016); the Readiness to Work with Trauma-Exposed Patients Scale (RTEPS) (Kazlauskas 2022); Brief Resilient Coping Scale (BRCS) (Sinclair & Wallston, 2004); Conjoint Community Resilience Assessment Measure (CCRAM) (Leykin et al. , 2013). Statistical processing of the data was carried out using descriptive statistics, regression and correlation analysis of the software tool IBM SPSS Statistics, 2023. The aprticipants were represented by a sample of senior students (n=85) of the Faculty of Psychology at Lesya Ukrainka Volyn National University who had clinicician’s or psychologist’s professional experience. The survey was carried out in September 2023 and was conducted online through a link on Google Forms. Results. The results indicate that shared is positively associated with shared trauma, professional post-traumatic growth and readiness to work with trauma.The results of the regression analysis show that shared trauma, posttraumatic growth, volunteering, having children, and personal experience of getting therapy are predictors of shared resilience. Conclusions. Moreover, learning and implementing the best practices of European Union to develop the applied psychologists’ shared resilience is of crucial importance in the context of shared traumatic reality in Ukraine.